Some geometric properties of a new difference sequence space defined by de la Vallee-Poussin mean - Et, Mikail; Karakas, Murat; Karakaya, Vatan (Elsevier Science Inc, 2014)
In this paper, wedefine a new generalized difference sequence space C-(p) Delta(m)(lambda) and consider it equipped with the Luxemburg norm under which it is a Banach space and we show that the space C-(p) Delta(m)(lambda) possess Banach Saks property of type p, uniform opial property and property (H), where p = (p(n)) is a bounded sequence of positive real numbers with pn > 1 for all n is an element of N. Also, we give some results about the fixed point theory for the spaces C-(p) D m d and C-p(Delta(m)) d (1
Keywords: Cesaro difference sequence space; Luxemburg norm; Banach Saks property; Convex modular; Property (H)